Factors predicting out-of-school suspensions for young children - Bell, Megan; Bayliss, Donna; Glauert, Rebecca; Ohan, Jeneva (International Journal of Population Data Science, 2018)
Introduction Despite limited evidence supporting the effectiveness of out-of-school suspension for rectifying behavioural issues, the practice continues. Certain demographic factors (male, ethnic minority, low SES) predict suspensions; however, developmental and family factors can also play a role. Knowledge of these factors may inform alternative practices aimed at limiting the practice of suspension. Objectives and Approach This study investigated the relationship between out-of-school suspensions and demographic, developmental, and family factors. Children suspended in early schooling may be particularly at risk of poor school outcomes; thus, our sample includes children in the first years of school. Linked administrative data were obtained for 14,269 children enrolled in grade 3 at public schools in Western Australia. Multilevel logistic regressions were run, grouped by school, with out-of-school suspensions predicted by: child and parent demographic characteristics; a measure of children’s school-entry development (the Australian Early Development Census); and indicators of family risk (parental psychiatric hospitalizations, parental criminal offending, child maltreatment). Results Approximately 2% of children had been suspended at least once by grade 3. Aboriginal children, boys, and children attending schools with high levels of socioeconomic disadvantage had significantly increased odds of being suspended from school (2 times, 6 times, and 3 times increase, respectively). Furthermore, children considered socially and emotionally vulnerable at school-entry were around 3 times more likely than their peers to be suspended in the first few years of school. Parental psychiatric hospitalizations, parental criminal offending, and child maltreatment all significantly predicted out-of-school suspensions. Odds increased exponentially with each additional family risk factor experienced in early childhood. Children experiencing all three family risk factors were almost 7 times more likely than their peers to be suspended at least once by grade 3. Conclusion/Implications Our results provide further justification for the implementation of alternatives to out-of-school suspension, as children who would most likely benefit from a stable, nurturing school environment were significantly more likely to be suspended. Schools need to be better supported by inter-agency collaboration to manage the complex needs of vulnerable children.